THU0151 Multicenter, Open-Label Study To Evaluate The Predictability of Disease Control at Week 52 Based on Early Response To Certolizumab Pegol (in Combination with Methotrexate) in Italian Patients with Moderate To Severe Rheumatoid Arthritis: The CZP-Speed Study. (15th July 2016) - Sarzi-Puttini, P.; Filippucci, E.; Adami, S.; Meroni, P.L.; Talavera, P.; Kumke, T.; Grassi, W.
Abstract : Background: Early identification of patients (pts) unlikely to achieve good long-term disease control with anti-TNF therapy in rheumatoid arthritis (RA) is important for physicians following treat-to-target recommendations. Predictability of response has previously been demonstrated in RA pts treated with certolizumab pegol (CZP), with previous work focusing on the predictability of long-term (1-year) response based on response at Week (Wk) 12. 1 In addition to clinical and patient-reported outcomes, musculoskeletal ultrasonography (US) is an increasingly important tool for assessing pt disease activity. Objectives: To assess the impact of CZP treatment on clinical, patient-reported and US outcomes, and to assess the ability of early treatment response to predict long-term outcomes in Italian pts with RA. Methods: CZP-SPEED (NCT01443364 ) was a 52-wk, open-label, prospective, interventional, multicenter study. Pts were biologic-naïve, had active RA (≥6 swollen and ≥6 tender joints), and had failed treatment with ≥1 DMARD. All pts received CZP (400mg at Wks 0, 2 and 4, followed by 200mg every 2 wks). Positive predictive value was defined as the percentage of pts with clinical response (reduction from baseline in DAS28(ESR)≥1.2) at an early time point who also had clinical response at Wk52. Early time points were Wks 1, 2, 4, 6, 8 and 12. Clinical and patient-reported outcomes were DAS28(ESR), ACR20/50/70, HAQ-DI, Pain (VAS) and PtGADA. US was assessed using the composite power Doppler/US (PDUS) score, defined as the sum of synovial fluid and proliferation, Doppler signal/blood flow, cartilage damage and bone erosion scores. US operation parameters were harmonized across all study sites. Data are reported descriptively with NRI imputation for dichotomous data and LOCF for continuous data. Results: 132 pts were enrolled and received CZP (safety set; SS), of whom 131 (99%) provided ≥1 baseline and ≥1 post-baseline DAS28(ESR) assessment (full analysis set; FAS), and 91 (69%) completed to Wk52. Pts had a mean age of 54.8, 82% were female, and disease duration was relatively short (median 1.8 years). Between 64–70% of pts who responded at Wk 2, 4, 6, 8, or 12 maintained response at Wk52 (Figure ). Rapid improvements in clinical and US outcomes were observed at Wk8 and were maintained to Wk52 (Table). There were 301 adverse events (AEs) in 94 pts (71.2%) and 25 serious AEs in 16 pts (12.1%). No deaths or cases of tuberculosis were observed. No new safety signals were observed for CZP. Conclusions: In Italian RA pts treated with CZP, clinical response up to Wk12 was predictive of long-term response at Wk52. In addition to the rapid and sustained clinical improvements observed in this cohort, this is the first report of the maintenance of US improvements over 52 wks in CZP-treated pts. Coupled with the clinical predictability data, US evaluation may allow rheumatologists to make decisions earlier in the treatment journey. References: Curtis J. Arthritis Care Res 2012;64:658–67 Acknowledgement: The authors acknowledge Costello Medical Consulting, funded by UCB Pharma, for writing and editorial assistance. Disclosure of Interest: P. Sarzi-Puttini: None declared, E. Filippucci Consultant for: UCB Pharma S.A., Bristol Myers Squibb, Merck Sharp & Dohme, AbbVie S.R.L. Italy, Roche, Pfizer, S. Adami: None declared, P. L. Meroni: None declared, P. Talavera Employee of: UCB Pharma, T. Kumke Employee of: UCB Pharma, W. Grassi Consultant for: UCB Pharma S.A., Bristol Myers Squibb, Merck Sharp & Dohme, AbbVie S.R.L, Pfizer